Pendidikan Hukum Masyarakat Melalui Kinerja Komisi Pemberantasan Korupsi - Alhudawi, Usman; Sujastika, Ismi (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2020)
The Corruption Eradication Commission (KPK) in addition to law enforcement agencies in the scope of corruption, also has a role to carry out anti-corruption education through legal education. The implementation of legal education is carried out in educational institutions and the community. This article describes the specifics of public legal education by the KPK through the KPK's performance from various literary sources. The research method used is qualitative. This research was conducted with a literature study with qualitative data collection techniques in the form of literature study (literature). Meanwhile, the data analysis process used is data reduction, data display, verification and conclusion drawing. The results show that the performance of legal education is given to students and the public. Due to the generality nature of legal education by the KPK, it becomes a role model for legal certainty in the community. This can be seen when the KPK has conveyed its wide-ranging performance in various mass media to provide meaning and experience in monitoring the implementation of national law by the public.—————Komisi Pemberantasan Korupsi (KPK) selain lembaga penegak hukum pada ruang lingkup tindak pidana korupsi, juga memiliki peran untuk melakukan pendidikan anti korupsi melalui pendidikan hukum. Pelaksanaan pendidikan hukum dilakukan di lembaga pendidikan dan dimasyarakat. Artikel ini membentangkan secara spesifik pendidikan hukum masyarakat oleh KPK melalui kinerja KPK dari berbagai sumber literatur. Metode penelitian yang digunakan adalah kualitatif. Penelitian ini dilakukan dengan studi literatur dengan teknik pengumpulan data kualitatif berupa studi pustaka (literatur). Sementara itu, proses analisis data yang digunakan adalan reduksi data, display data, verifikasi dan penarikan kesimpulan. Hasil menunjukan bahwa kinerja pendidikan hukum diberikan untuk kalangan pelajar dan mahasiswa serta masyarakat. Karena sifat keumuman Pendidikan hukum oleh KPK menjadi role model kepastian hukum masyarakat. Hal tersebut tampak tatkalah KPK menyampaikan kinerjanya luas diberbagai media massa sehingga memberi makna dan pengalaman memantau pelaksanaan hukum nasional oleh masyarakat.